Prevalence, correlates, psychiatric comorbidities, and suicidality in a community population with problematic Internet use - Kim, Byung-Soo; Chang, Sung Man; Park, Jee Eun; Seong, Su Jeong; Won, Seung Hee; Cho, Maeng Je (Psychiatry research, 2016)
We examined the prevalence, correlates, and psychiatric comorbidities of community-dwelling subjects with problematic Internet use (PIU). In an epidemiological survey of mental disorders among Korean adults conducted in 2006, 6510 subjects (aged 18–64 years) completed the Korean version of the Composite International Diagnostic Interview for DSM-IV psychiatric disorders; Diagnostic Interview Schedule exploring pathological gambling; Adult ADHD Self-Report Scale-Version 1.1 Screener; questionnaire for sleep disturbances; and questionnaire for suicidal ideations, plans, and attempts. Young's Internet Addiction Test was administered to 3212 individuals who had used the Internet within one month before the interviews in order to identify problematic Internet users (cutoff >39). The prevalence of PIU was 9.3% in the general population of South Korea. Being male, younger, never married, or unemployed were all associated with increased risks of PIU. Significant positive associations were observed between PIU and nicotine use disorders, alcohol use disorders, mood disorders, anxiety disorders, somatoform disorders, pathological gambling, adult type ADHD symptoms, sleep disturbances, suicide ideas and suicide plans compare to subjects without PIU, after controlling for socio-demographic variables. These findings suggest that careful evaluation and management of such psychiatric disorders is needed for individuals with PIU. •Problematic Internet use (PIU) is very common in the general population.•Individuals with PIU were more likely to have psychiatric disorders or symptoms.•These psychiatric disorders should be thoroughly screened for in persons with PIU.